Prevence casné formy onemocnení novorozenců streptokoky skupiny B: neonatální outcome po zavedení doporuceného postupu - Simetka, O; Petros, M; Podesvová, H (Ceska gynekologie, 2010)
OBJECTIVE: To evaluate the effectiveness of introduction of national guideline to prevent early-onset group B streptococcal (EOGBS) disease, number of screened women and incidence of GBS colonization. DESIGN: Retrospective cohort study. SETTING: Department of Obstetrics and Gynaecology, Department of Neonatology, University Hospital Ostrava. SUBJECT AND METHOD: We reviewed 8484 consecutive term pregnancies of women who delivered in our hospital, between years 1999-2001 before the introduction of guideline and years 2003-2005 following the guideline. RESULTS: In group 1999-2001 there were 12/3581 (3.35 per thousand) neonates with EOGBS infection in which 7/3581 (1.96 per thousand) had invasive disease. In group 2003-2005 there were 14/4903 (2.86 per thousand) neonates with EOGBS infection (p=68,33%), in which 6/4903 (1,22 per thousand) had invasive disease (p=39,52%). Number of screened women in years 2003-2005 increased from 40% to 65%, and 69% respectively. There were 577/3019 (19%) of GBS colonized women. CONCLUSION: There was 15% decrease of EOGBS disease following the introduction of guideline. Number of screened women increased by 29% in three-year period. GBS colonization in pregnant women is 19%.
Keywords: vertikální přenos infekce; Pregnancy Complications, Infectious; novorozenec; Infant, Newborn; Pregnancy; Humans; Female; Neonatal Screening; infekční komplikace v těhotenství; Infectious Disease Transmission, Vertical; lidé; novorozenecký screening; Streptococcus agalactiae; streptokokové infekce; Streptococcal Infections; Practice Guidelines as Topic; ženské pohlaví; těhotenství; Czech Republic; směrnice pro lékařskou praxi jako téma; Česká republika